THE EFFECT OF AUGMENTED REALITY-BASED AUTOMATIC TRANSMISSION MEDIA ON BASIC KNOWLEDGE - Komarudin, Komarudin; Nauri, Imam Muda; Mardji, Mardji; Mindarta, Erwin Komara; Ariyanto, Sudirman Rizki (STKIP PGRI Tulungagung, 2024)
Innovative and interactive learning media was needed to graduate a workforce that was in accordance with the world of work. Automatic Transmission based on Augmented Reality operated using a smartphone can help students know the components, functions and workings of AT. Augmented Reality is an application that combines the real world with the virtual world in the form of two dimensions or three dimensions projected in a real environment at the same time. Smartphones can be a digital media in delivering material. This research uses the ADDIE development model. This research aims to develop Automatic Transmission media based on Augmented Reality. AT media was evaluated by media experts, automotive experts and students. The validity test results show that AT media was valid according to media experts and automotive experts. This study aims to develop this media to help students master the prior knowledge of AT material. ANOVA test results show that AT AR media has an effect on prior knowledge. AT AR media was attractive, easy to operate using a smartphone and improves the ability to mention the names of AT components, explain the functions and workings of AT.